Eighteen years of molecular genotyping the hemophilia inversion hotspot: from southern blot to inverse shifting-PCR - Rossetti, Liliana Carmen (2011)
The factor VIII gene (F8) intron 22 inversion (Inv22) is a paradigmatic duplicon-mediated rearrangement, found in about one half of patients with severe hemophilia A worldwide. The identification of this prevalent cause of hemophilia was delayed for nine years after the F8 characterization in 1984. The aim of this review is to present the wide diversity of practical approaches that have been developed for genotyping the Inv22 (and related int22h rearrangements) since discovery in 1993. The sequence- Southern blot, long distance-PCR and inverse shifting-PCR-for Inv22 genotyping is an interesting example of scientific ingenuity and evolution in order to resolve challenging molecular diagnostic problems.